2015
DOI: 10.1007/s10522-015-9577-9
|View full text |Cite
|
Sign up to set email alerts
|

No strong correlations between serum cytokine levels, CMV serostatus and hand-grip strength in older subjects in the Berlin BASE-II cohort

Abstract: Hand-grip strength is strongly correlated with measures of muscle mass and can be taken to predict morbidity and mortality. The aim of this study was to investigate the relationship between hand-grip strength and other markers associated with immune ageing, such as Cytomegalovirus (CMV) infection, leukocyte telomere length and serum levels of inflammatory and anti-inflammatory markers in the elderly. We have assessed grip strength with the Smedley Dynamometer in younger (22-37 years) and older (60-85 years) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Some studies have found that human CMV infection in older individuals is associated with increased cardiovascular and all-cause mortality, negative immune risk profile, inflammageing, and lower antibody responses to influenza 125129 . However, evidence that the association between CMV infection and CVD and mortality is mediated by inflammageing is scant at best 109,130 . The theoretical CMV-associated impaired capacity to control heterologous infections in old age and the association with high circulating levels of pro-inflammatory cytokines have also been challenged 109 .…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 99%
“…Some studies have found that human CMV infection in older individuals is associated with increased cardiovascular and all-cause mortality, negative immune risk profile, inflammageing, and lower antibody responses to influenza 125129 . However, evidence that the association between CMV infection and CVD and mortality is mediated by inflammageing is scant at best 109,130 . The theoretical CMV-associated impaired capacity to control heterologous infections in old age and the association with high circulating levels of pro-inflammatory cytokines have also been challenged 109 .…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 99%
“…For example, PCR-based methods are less sensitive to possible epigenetic differences between men and women that may influence recognition sites for restriction endonucleases used in other methods. It is noteworthy that a different study that also used a PCR-based methodology for measuring TL recently observed longer telomeres in men in another German cohort of older individuals [ 26 ]. On the other hand, not all studies that used PCR-based methodology found longer telomeres in men [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum cytokine levels were determined as described previously (29,57). Brie y, cytokine levels of IL-1ß, IL-6, IL-10 and TNFα were determined using the high sensitivity CBA ex system (BD Biosciences), according to the manufacturer´s instructions.…”
Section: Cytokine Analysismentioning
confidence: 99%